Viscosity of vegetable oils in methyl ethyl ketone and tetrahydrofuran - Trinh, T.H. (Japan Institute of Energy, 2017)
The transesterification of vegetable oil can be accelerated when conducting in single phase because it eliminates the mass transfer control. The size of the alkyl group of triglyceride can affect the reaction rate in this region since larger (bulky) alkyl group hiders another reactant methanol from approaching the ester bond. Viscosity of a solution is a convenient method to indirectly estimate the size of the solute in the solution. The current work investigates the viscosity of the solutions with different vegetable oil concentrations in two solvents, i.e., methyl ethyl ketone and tetrahydrofuran. The Huggins equation has been then applied to determine the intrinsic viscosity and the Huggins constant which are related to the size of the solute and the intermolecular interaction of solute in the solution, respectively. According to the results, intrinsic viscosities of vegetable oils increase following the order coconut oil (CO), sunflower oil (SF), and palm oil (PO). However, the intermolecular interaction is following the reverse order. This result is in accordance with our previous research on the relationship between molecular weight of triglyceride and its transesterification reaction rate in methyl ethyl ketone. © 2017, Japan Institute of Energy. All rights reserved.